The Use of Pheromones and Lamps as Traps for Rhinoceros Beetles (Oryctes rhinoceros) in Young Oil Palm Plants - Santi, Idum Satia; Rianto, Rianto; Manto, Agus (Akademi Komunitas Perkebunan Yogyakarta, 2025)
The rhinoceros beetle (Oryctes rhinoceros) is a fairly important pest in oil palm plants, especially in young or unproductive plants. The purpose of this study is to examine the use of pheromones and lamps as horn beetle traps. The research was carried out in a community plantation in Sungai Lala, Kelawat District, Indragiri Hulu, Riau. The research was carried out for 1 month, with tools in the form of lamp traps and pheromones, as well as a combination of both. The results showed that the combination of pheromones with trap lights provided the most catch compared to single treatment. There was no difference in the catch of male and female beetles in all treatments. It is hoped that the results of this research can be used to control rhino beetles in a simple way in community plantations.